Analysis of Performance Improvement on PT. Distribusi Air Santri (PT. DAS) Using Business Model Canvas - Zeniar Adzmizah; Moses Laksono Singgih (Institut Teknologi Sepuluh Nopember, 2020)
Since 1975, the drinking habits of the Indonesian people began to change from being merely boiling water from tap to bottled water (AMDK), thus encourage drinking water producers to continue branch out in market share. In 2013, the market share of AMDK industry was Rp 22.51T and there were around 500 competing AMDK companies. PT. Distribusi Air Santri (PT. DAS) is a company engaged in the distribution of “Air Mineral Santri” brand which located in Surabaya. This company aims to increase the market in Surabaya by 10% or sell 142,000 items / month. So to achive company goals, company need to develop business models and plan business strategies using Business Model Canvas (BMC). In the BMC analysis, an analysis of environmental conditions was carried out using the 7sMcKinsey method, External Scanning and porter strength analysis. And validation is needed so that BMCs are made accurately and precisely with the help of a SWOT analysis.